A preliminary study on the patients’ experiences in receiving spiritual care at shari’ah compliance hospital - Wan Mamat, Wan Hasliza; Hairulisa@Mohd Hairi, Nur Alia; Mohamad Shariff, Nurasikin; Jaafar, Siti Nur Illiani; Che Ahmad, Aminudin; Salah, Machouche (Universiti Putra Malaysia, 2025)
Introduction: Spiritual care has been recognised as a critical component influencing the overall well-being of patients. Previous research suggests that integrating spiritual care into patient management offers multiple benefits, including improved mental health, reduced levels of anxiety and depression, and enhanced quality of life. Although several studies have examined the outcomes of spiritual care interventions, limited attention has been given to understanding the lived experiences of patients receiving spiritual care during hospitalisation. This study aims to explore patients’ experiences of spiritual care during their hospital stay. Methods: This study employed a qualitative research design. Ten participants were recruited through nominations by healthcare providers who had previously delivered spiritual care. Participants engaged in one-time, in-depth, face-to-face interviews, which were audio-recorded with consent. All interviews were transcribed verbatim and subsequently analysed using thematic analysis. Results: Two major themes emerged regarding patients’ experiences of spiritual care: (1) Challenges in addressing spiritual needs, and (2) Approaches utilised to deliver spiritual care. The findings reveal that hospitalised patients frequently experience feelings of hopelessness and loneliness. However, compassionate care provided by healthcare professionals significantly contributes to improving their emotional and spiritual well-being. Conclusion: Hospitalised patients require not only medical treatment but also spiritual support to promote holistic recovery. Gaining an understanding of patients’ experiences is crucial for healthcare providers in delivering effective spiritual care, addressing service gaps, and promoting patient-centred care. Further research is warranted to develop comprehensive strategies for integrating spiritual care into routine clinical practice.